2005
DOI: 10.1016/j.visres.2004.08.008
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of elevated intraocular pressure on mouse retinal ganglion cells

Abstract: We developed and characterized a mouse model of elevated intraocular pressure (IOP) to investigate the underlying cellular and genetic mechanisms of retinal ganglion cell (RGC) death. IOP was unilaterally increased in C57BL/6J mice by photocoagulation of the episcleral and limbal veins. IOP was measured using an indentation tonometer. RGC survival was measured by retrograde labeling using DiI applied to the superior colliculous. The mechanism of RGC death was investigated using TUNEL staining, immunostaining f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 26 publications
3
51
1
Order By: Relevance
“…Our results have shown that functional changes of the DBC R →AIIAC synapses are likely to be a primary source of RGC sensitivity loss in mice with elevated IOP. We found such sensitivity reduction in ON and OFF αGCs as well as in AIIACs in mice with elevated IOP at stages before significant RGC or optic nerve degeneration is observed (12,16). This suggests that physiological response changes may occur before structural damage in early stages of glaucoma, and thus measuring RGC and AIIAC response sensitivity changes may be used as a diagnostic tool for glaucoma at its early stages before any irreversible structural damage occurs.…”
Section: Sensitivity Loss In Inner Retinal Neurons Occurs Before Obsementioning
confidence: 60%
See 2 more Smart Citations
“…Our results have shown that functional changes of the DBC R →AIIAC synapses are likely to be a primary source of RGC sensitivity loss in mice with elevated IOP. We found such sensitivity reduction in ON and OFF αGCs as well as in AIIACs in mice with elevated IOP at stages before significant RGC or optic nerve degeneration is observed (12,16). This suggests that physiological response changes may occur before structural damage in early stages of glaucoma, and thus measuring RGC and AIIAC response sensitivity changes may be used as a diagnostic tool for glaucoma at its early stages before any irreversible structural damage occurs.…”
Section: Sensitivity Loss In Inner Retinal Neurons Occurs Before Obsementioning
confidence: 60%
“…2B) and ΔI C and ΔI Cl (Fig. 2 C and D, respectively) of an ONαGC to light steps of various intensities in a darkadapted flat-mounted retina of a mouse with 5-wk elevated IOP (15-24 Hg) (12,16). The average response-intensity (R-Log I) relations of six ONαGCs in H-IOP mouse retinas (with 3-to 7-wk elevated IOP, four with the laser method and two with the microbead method; Materials and Methods) are shown as dotted curves in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A transgenic (Tg) mouse strain with a targeted mutation in the gene for the ␣1 subunit of collagen type I demonstrates a gradual elevation of intraocular pressure (IOP) and progressive optic nerve axon loss (Mabuchi et al, 2004). Other approaches include cauterization of the episcleral and limbal veins leading to elevation of IOP and the loss of RGCs (Ji et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…First, we show that exposing conscious animals to intermittent systemic hypoxia, a noninvasive postconditioning stimulus, can promote glaucoma resistance without the requirement for inducing repetitive anesthesia and/ or repetitive, direct retinal ischemia. Second, we demonstrate postconditioning efficacy in a model of glaucoma exhibiting progressive, time-dependent RGC loss secondary to IOP elevation by a relatively common episcleral vein occlusion approach [9][10][11][39][40][41][42][43][44], in contradistinction to a more obscure model dependent on weekly anterior chamber injections of chondroitin sulfate to elevate IOP [38]. Third, we now document that glaucomatous protection by postconditioning is feasible in mice.…”
Section: Discussionmentioning
confidence: 82%